Combination of two learning approaches which are Self-Regulated Learning and Personalized Learning (SRPL) - Ali, Mohamad Bilal (2012)
Nowadays, learning trend by using internet is increasing especially in higher educational level. The old learning strategy which is practiced in traditional way like face-to-face learning in class should be change to ensure that it can be applied in learning based on internet technology. One of that learning approaches is self-regulated learning. Previously, self-regulated learning was adapted in learning without being supported by any other learning approaches. Lately, there is a learning approach known as SelfRegulated Personalized Learning (SRPL) in which, this learning approach is a combination of two learning approaches which are self-regulated learning and personalized learning. In general, this paper will be discussing about the combination of two learning approaches which are self-regulated learning and personalized learning.